Development of high performance and defect-free asymmetric polyethersulfone membranes for O2/N2 separation - Ridzuan, Norida (2004)
The objective of this study is to develop high performance and defect-free asymmetric polyethersulfone (PES) membranes for O2/N2 separation by manipulation of phase inversion process and rheological factors, including different type of nonsolvent additives, polymer concentration, shear rate and evaporation time. Asymmetric flat sheet membranes were fabricated using a pneumatically-controlled casting machine through a simple dry/wet phase inversion process. 1-methyl–2- pyrolidone (NMP) was employed as a solvent while distilled water (H2O) and ethanol (EtOH) were used as nonsolvent additives (NSA). For the first stage of this study, three types of casting solution using H2O as NSA and three types of casting solution using EtOH as NSA had been formulated through titration method. On the next stage, the membranes were fabricated at constant shear rate and evaporation time which is 233.37 s-1 and 12s respectively. Consequently, from the pure gas permeation test results, it was found that the optimum weight percent of PES in casting solution were 32.62 wt% and 26.71 wt % when H2O and EtOH were used as NSA, respectively. Both of the casting solutions were chosen for optimizing the effect of shear rate and evaporation time. Finally, the membranes were fabricated at five different shear rates ranging from 111.67s-1 to 744.44s -1 and at six evaporation times ranging from 8s to 20s. The results showed that as the shear rate increased, the selectivity and pr essure-normalized flux increased until critical shear rate was reached. The best shear rate was found at 233.33s -1 and 148.89s-1 when H2O and EtOH were used as NSA, respectively. The rheologicaly induced molecular orientation in asymmetric membranes was observed by analyzing the wave length showed by Attenuated Total Reflection Fourier Transform Infrared Spectroscopy (FTIR-ATR). On the other hand, as evaporation time was increased, the selectivity would increase but the pressure-normalized flux would decrease. The best evaporation time was found at 12s for both casting solution. Thus, the different NSA showed different influence on gas separation characteristics and structures of the produced membranes. The newly developed PES membranes with new casting solution formulation that used H2O as the NSA, exhibited O2/N2 selectivity and pressure -normalized flux at about 7.95 and 9.71 GPU for O2 respectively. The average skin layer thickness of these membranes was approximately 538.32Å. As for the membranes using EtOH as NSA, the O2/N2 selectivity and pressurenormalized flux were 5.01 and 14.07 GPU for O2, respectively. The calculated average skin layer thickness was about 369.77Å. Therefore, the PES membranes prepared from NMP/H2O solvent systems proved to provide the best separation characteristics compared to those membranes produced from NMP/ EtOH solvent system. As a conclusion, the combination of phase inversion process and rheological factors had successfully developed high performance, defect-free and hyperthinskinned layer PES asymmetric membranes for O2/N2 separation.